Dental and Craniofacial Anatomical Variations and Their Impact on Orthodontic Diagnosis and Treatment Planning: A Systematic Review - Sovira, Gita Dwi Jiwanda; Putri, Wulandani Liza; Yona Ladyventini (Sean Institute, 2025)
Background: Dental and craniofacial anatomical variations are fundamental determinants of orthodontic diagnosis and treatment planning. Variability in tooth morphology, skeletal relationships, and alveolar bone anatomy may influence biomechanical feasibility, treatment selection, and the risk of complications. Objective: This systematic review aimed to synthesize current evidence on dental and craniofacial anatomical variations and to evaluate their impact on orthodontic diagnosis and treatment planning. Methods:A systematic literature search was conducted in PubMed, Scopus, and Web of Science in accordance with the PRISMA 2020 guidelines. Studies published in English within the last 10 years and involving human subjects with permanent dentition were considered. Data extraction and study selection were performed independently, and findings were synthesized narratively due to methodological heterogeneity. Results: Twenty studies were included in the qualitative synthesis. Dental anatomical variations, particularly root morphology and tooth anomalies, were associated with biomechanical limitations and increased risk of root resorption. Craniofacial skeletal variations influenced malocclusion patterns, growth assessment, and decisions between orthodontic camouflage and combined orthodontic surgical treatment. Alveolar bone anatomical variability defined the biological limits of orthodontic tooth movement and was closely linked to periodontal risk. 3D imaging techniques, especially cone-beam computed tomography, enhanced the identification of clinically relevant anatomical constraints. Conclusions: Dental, craniofacial, and alveolar anatomical variations play a critical role in orthodontic diagnosis and treatment planning. An anatomy driven approach supported by appropriate imaging improves diagnostic accuracy, facilitates individualized treatment strategies, and reduces the risk of adverse outcomes. These findings support the integration of comprehensive anatomical assessment into precision orthodontic practice.